Pengembangan Kualitas Perguruan Tinggi Islam Berdasarkan Keinginan dan Kebutuhan Stakeholder - Septin Puji Astuti; Datien Eriska Utami (JAS-PT (Jurnal Analisis Sistem Pendidikan Tinggi Indonesia), 2018)
Islamic University have to enhance their quality to make it more survive in this globalisation era. Consequently, it is important to identify the performance of the university. Apart from that, university stakeholder voices are important to be heard and it can be involved to increase the quality of higher education. For that reason, the main aim of this research is to identify Islamic university performance regarding to external stakeholder point of views. Hence, this research applied important-performance analysis to formulate the strategies for lifting the quality of university. For that purpose, 130 external stakeholders were gathered to be interviewed. Finally, it is found thatthe university has to pay more attention to improve the performance of computer facilities, their responsiveness to the development of the world and the fitness of curriculum to real world environment. Kata Kunci: strategi, analisis impotance-performance, stakeholder needs and wants